High kinesin family member 11 expression predicts poor prognosis in patients with clear cell renal cell carcinoma. Issue 5 (28th February 2019) - Jin, Qin; Dai, Yanfeng; Wang, Yan; Zhang, Shu; Liu, Gang
Abstract : Aims: Kinesin family member 11 (Kif11) is a member of the kinesin family motor proteins, which is associated with spindle formation and tumour genesis. In this study, we investigated the relationship between Kif11 expression and clear cell renal cell carcinoma (CCRCC) development. Methods: The relationship between Kif11 expression and CCRCC development was analysed by quantitative real-time (qRT)-PCR analyses, and tissue immunohistochemistry. The prognostic significance of Kif11 expression was explored by univariable and multivariable survival analyses of 143 included patients. Furthermore, SB743921 was used as a specific Kif11 inhibitor to treat 786-O cells with the epithelial to mesenchymal transition (EMT) process analysed by qRT-PCR, and cell survival rates analysed with Annexin V-FITC/PI staining followed by flow cytometric analyses. Disease-free survival curves of Kif11 with different cancers and the relationships between Kif11 and the von Hippel-Lindau disease tumour suppressor gene ( VHL ), and proliferating cell nuclear antigen (PCNA) in kidney cancer were further analysed using the GEPIA database. Results: The levels of Kif11 mRNA were significantly higher in CCRCC tissues compared with corresponding non-cancerous tissues. The results of immunohistochemistry demonstrated that the expression of Kif11 protein was significantly associated with clinicopathologial parameters, including nuclear grade and TNM stage. The Kaplan-Meier survival curve indicated that high Kif11 expression, nuclear grade and TNM stage were independent factors to predict poor prognosis in patients with CCRCC. In addition, inhibition of Kif11 expression by SB743921 suppressed cell proliferation, migration and the EMT process with increased apoptosis rate. Conclusions: These results combined with bioinformation analyses suggest that high Kif11 expression was associated with unfavourable prognosis in CCRCC and could be used as a potential prognostic marker in the clinical diagnosis of CCRCC.